2022
DOI: 10.1002/ldr.4439
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometric characteristics of medium‐ and micro‐elements (Ca, Mg, Fe, and Mn) in soil aggregates as affected by stand age in Chinese fir plantations

Abstract: In order to understand the fertility of soil comprehensively in Chinese fir plantations, the stoichiometric characteristics of soil nutrient elements should be paid more attention to. Despite the broad investigation of the stoichiometry regarding soil C, N, P, and K, the stoichiometry regarding soil Ca, Mg, Fe, and Mn remains unclear.Therefore, this research aimed at exploring how the medium-and micro-element (Ca 2+ , Mg 2+ , Fe 2+ , and Mn 2+ ) contents, stocks, and their stoichiometric ratios (Ca 2+ / Mg 2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The 2011–2018 monitoring data regarding the precipitation in Guangxi revealed that sulfurous acid rain constituted the precipitation in Guangxi, mainly observed in northern region and western region (Huang et al, 2019). In our research region (located in northern Guangxi) (Figure 1), frequent acid rain made soil exchangeable Ca and Mg to loss (Wang et al, 2022), and then resulted in soil acidification (Bini & Bresolin, 1998). Moreover, the rhizodeposition of substantial organic acids (like oxalate acid, lemon acid, and malic acid) around tree roots could elicit localized soil acidification, especially at the late stage of Chinese fir growth (Augusto et al, 1998).…”
Section: Discussionmentioning
confidence: 92%
“…The 2011–2018 monitoring data regarding the precipitation in Guangxi revealed that sulfurous acid rain constituted the precipitation in Guangxi, mainly observed in northern region and western region (Huang et al, 2019). In our research region (located in northern Guangxi) (Figure 1), frequent acid rain made soil exchangeable Ca and Mg to loss (Wang et al, 2022), and then resulted in soil acidification (Bini & Bresolin, 1998). Moreover, the rhizodeposition of substantial organic acids (like oxalate acid, lemon acid, and malic acid) around tree roots could elicit localized soil acidification, especially at the late stage of Chinese fir growth (Augusto et al, 1998).…”
Section: Discussionmentioning
confidence: 92%
“…According to the precipitation monitoring data from 2011 to 2018 in Guangxi, sulfurous acid rain was the primary type of acid rain, and it mainly occurred in northern and western Guangxi (Huang et al, 2019). The experimental area in this study is situated in northern Guangxi (Figure S1), where recurrent acid rain contributes to the depletion of soil exchangeable Ca 2+ and Mg 2+ , which leads to the intensification of soil acidification (Wang et al, 2022). Additionally, organic acids' (including malic acid, oxalate acid, and lemon acid) deposition around Chinese fir roots may also contribute to the rhizosphere soil acidification (Augusto et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Aggregate composition and stability are critical for assessing soil structure, which in turn affects nutrient supply, storage, and erosion resistance (Fattet et al, 2011). Larger aggregates improve soil stability and pore structure, while an increase in microaggregates can elevate the risk of soil erosion (Zhang et al, 2008;Wang et al, 2022).…”
Section: Effects Of Mixed Forests On Soil Aggregate Stability and P D...mentioning
confidence: 99%
“…Consequently, these mixed forests showed improved soil quality metrics, such as higher MWD and GMD of aggregates (Al-Kaisi et al, 2014;Giumbelli et al, 2020) (Table 4). The physical and chemical attributes of soil structure and biological factors play a pivotal role in determining soil stability (Wang et al, 2022). In mixed Eucalyptus forests, increased plant diversity often supports a broader range of soil fauna and flora.…”
Section: Effects Of Mixed Forests On Soil Aggregate Stability and P D...mentioning
confidence: 99%
See 1 more Smart Citation